Managing financial risks while performing international commercial transactions: Intertemporal lessons from Athens in classical times - Emmanouil Marios L. Economou; Nikolaos A. Kyriazis; Nikos K. Kyriazēs (Journal of Risk and Financial Management, 2021)
In this paper, we mainly focus on two institutional aspects that are related to financial risk, that is, profiteering and the use of non-fraudulent coins when performing financial transactions. We argue that these two prerequisites were important for the success of the commercially oriented economy of the Athenian state in comparison with its allies in the East Mediterranean during the classical period. In particular, we briefly explain the structure of the Athenian economy, and then we focus on the agoranomoi and the dokimastai, the two main financial institutions related to (i) measures against profiteering and (ii) ensuring the purity of the currency when performing commercial transactions. Then, following a game theoretical approach, we provide a fictional example as to how the two institutions functioned in practice. Our findings confirm that these institutions were crucial in reducing financial risk when performing international commercial transactions, since they provided symmetrical information on the quality and purity of the currencies circulating in the Athenian economy. In the case of the Athenian state, we further convey that measures against profiteering and the use of unadulterated currency comprise intertemporal axioms, in the sense that their importance is not merely a phenomenon of modern times, but rather, on the contrary, one that dates back to much earlier times.
Keywords: D81; G28; N23; N43; 330; financial risk; financial institutions; international commerce; profiteering; non-fraudulent currency; classical Athens